Proceedings, IEEE Aerospace Conference
DOI: 10.1109/aero.2002.1036155
|View full text |Cite
|
Sign up to set email alerts
|

Surface mounted and scanning periodic field eddy-current sensors for structural health monitoring

Abstract: Many aircraft components originally designed to last the design life of the aircraft without experiencing cracking (i.e., safe-life components) are now failing in service due to multiple site damage in locations not considered critical in original fatigue evaluations. For safelife components that must now he managed by damage tolerance methods, periodic inspections are generally far more costly than for components originally designed with planned inspection% Often. the high cost of these inspections is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Additionally, the software and signal conditioning tools necessary to locate and image the damage was far too complicated to efficiently function in a SHM system. Goldfine et al [8] performed a similar study, in which the authors used MWM sensors to identify cracks induced in an aluminum specimen subjected to bending fatigue. The results of the study showed that the cracks could be detected but once again the sensor was required to be positioned directly above the damage location.…”
Section: Cost In Billions Of Dollarsmentioning
confidence: 99%
“…Additionally, the software and signal conditioning tools necessary to locate and image the damage was far too complicated to efficiently function in a SHM system. Goldfine et al [8] performed a similar study, in which the authors used MWM sensors to identify cracks induced in an aluminum specimen subjected to bending fatigue. The results of the study showed that the cracks could be detected but once again the sensor was required to be positioned directly above the damage location.…”
Section: Cost In Billions Of Dollarsmentioning
confidence: 99%
“…To address the different SHM levels, a variety of SHM techniques is available, including, but not limited to, acoustic emission (AE), 1,2 guided waves, 35 strain sensing, 6,7 vibration-based methods, 810 eddy currents, 1113 and electrical impedance tomography. 1416 Each technique has its own strengths and the selection of SHM techniques should rely on its application purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Jentek Sensors developed a meandering winding magnetometer (MWM) sensor by using the flexible circuit manufacturing process, and that sensor is suitable for detecting the damage and thickness of conductive materials. The sensor has been used for stress monitoring and structural fatigue crack monitoring of ferromagnetic materials [17] and structural fatigue crack monitoring [18]. Rakow et al [19] developed a SHM bolt that consists of an eddy current sensor film integrated with the bolt, and it was used for crack monitoring of a bolt hole in a wall.…”
Section: Introductionmentioning
confidence: 99%